Relevansi Gereja: Mendorong Pertumbuhan Spiritualitas Generasi Z di Tengah Budaya Individualisme - Wulur, Hersen Geny (STT Internasional Harvest Tangerang, 2024)
Generation Z shows strong characteristics of individualism, reflected in their high freedom of speech, strong self-autonomy, and tendency to live self-centered lives. They typically dislike being hindered and are accustomed to doing everything themselves to achieve their personal goals. This research aims to explore how individualism influences the spiritual growth of Generation Z. Research using a qualitative approach with literature review methods reveals that Generation Z tends to view religion or church as something more personal and less relevant in their daily lives. Negative stereotypes about the church arise due to their perception that their freedom of speech is hindered, leading to feelings of spiritual and religious oppression. To address these challenges, churches need to adopt approaches that meet the needs of Generation Z. Based on the results of the literature review analysis, it appears that through mentoring and building healthy communities, churches can create environments that support Generation Z in developing their own spirituality.